2020
DOI: 10.31332/lkw.v6i1.1528
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse Markers in Scientific Journal Articles

Abstract: This paper aimed to investigate the use of metadiscourse markers in scientific journal articles. Data of this qualitative research consisted of metadiscourse markers collected from eight journal articles of a special edition published by LLT Journal: A Journal on Language and Language Teaching.  The collected metadiscourse markers used in the journal articles were analyzed using discourse analysis based on ten metadiscourse marker categories. Results showed that the analysed journal articles contained 708 meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Akoto and Afful (2020) discovered the following hierarchy for interactive markers: evidential, endophoric, transitional and frame markers. Nugrahani and Bram (2020) investigated eight published English language articles. The articles were analyzed manually to find which type and subtype of met adiscourse appeared more frequently.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Akoto and Afful (2020) discovered the following hierarchy for interactive markers: evidential, endophoric, transitional and frame markers. Nugrahani and Bram (2020) investigated eight published English language articles. The articles were analyzed manually to find which type and subtype of met adiscourse appeared more frequently.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Initially, everyone concentrated on one, two or three segments within the articles they examined. For example, Benraiss and Koumachi (2023) and Musa et al (2019) focused on one section, Akoto and Afful (2020) and Nugrahani and Bram (2020) studied two sections and Alharbi (2021) investigated three sections. This may affect the examined data and accordingly may not yield the required resul ts.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Thus, there is a need to create awareness of the use of metadiscourse in various settings. Some researchers have conducted studies related to metadiscourse awareness, such as Karakus (2020), Nugrahani andBram (2020), andPrommas (2020), who conducted studies on awareness of both interactive and interactional metadiscourse. The findings of those studies may be used to determine future instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For evidentials (or attributors), Nugrahani and Bram (2020) mentioned that these attributors are important linguistic elements in writing because citation of other writers' work provides credibility to the writer's own writing. Hence, The Star Online writers achieved the awareness required for citing materials from other sources because they had the highest mean score in identifying attributors For Focus Malaysia, the highest mean score was displayed by attributors and attitude markers categories (M = 3.000), while the second highest mean score was displayed by commentaries category (M = 2.833).…”
Section: Interpersonal Metadiscoursementioning
confidence: 99%
“…Its appeal among researchers and academics who study speech analysis has been demonstrated in few scholarly works (Nugrahani & Bram, 2020;Liu & Buckingham, 2018;Albalat-Mascarell & Carrió-Pastor, 2019;Mirzaeian, 2020;Farahani & Kazemian, 2021) Several metadiscourse analysts were interested in published scientific articles or those who were interested in investigating metadiscourse in academic publications (Jalilifar et al, 2018;Carrio-Pastor, 2019;Almudhaffari et al, 2019). Some scholars (Alkhodari & Habil, 2021;Kuswoyo & Siregar, 2019;Zhang et al, 2017) have focused on the analysis of metadiscourse in spoken discourse, as well as on less significant issues like the use of metadiscourse in online advertisements (Al-Subhi, 2022), interactional metadiscourse based on gender (Suhono & Haikal, 2018), and English instruction manuals (Herriman, 2022).…”
Section: Introductionmentioning
confidence: 99%